Physiological Role for the GlnK Protein of Enteric Bacteria: Relief of NifL Inhibition under Nitrogen-Limiting Conditions - He, Luhong (American Society for Microbiology, 1998)
In Klebsiella pneumoniae, NifA-dependent transcription of nitrogen fixation (nif) genes is inhibited by a flavoprotein, NifL, in the presence of molecular oxygen and/or combined nitrogen. We recently demonstrated that the general nitrogen regulator NtrC is required to relieve NifL inhibition under nitrogen (N)-limiting conditions. We provide evidence that the sole basis for the NtrC requirement is its role as an activator of transcription for glnK, which encodes a P(II)-like allosteric effector. Relief of NifL inhibition is a unique physiological function for GlnK in that the structurally related GlnB protein of enteric bacteria—apparently a paralogue of GlnK—cannot substitute. Unexpectedly, although covalent modification of GlnK by uridylylation normally occurs under N-limiting conditions, several lines of evidence indicate that uridylylation is not required for relief of NifL inhibition. When GlnK was synthesized constitutively from non-NtrC-dependent promoters, it was able to relieve NifL inhibition in the absence of uridylyltransferase, the product of the glnD gene, and under N excess conditions. Moreover, an altered form of GlnK, GlnK(Y51N), which cannot be uridylylated due to the absence of the requisite tyrosine, was still able to relieve NifL inhibition.